2015
DOI: 10.1177/0731684415592261
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the effect of fiber orientation on hydrostatic buckling behavior of fiber metal composite cylinder

Abstract: The external hydrostatic buckling behavior of fiber metal laminate (FML) composite cylinders was investigated numerically. The critical buckling pressure predicted by eigenvalue analysis was compared with experimental results. The numerical results showed different modes of buckling and buckling deformation for cylinders of different fiber orientation when subjected to external hydrostatic loading. FML cylinder with 0 /90 fiber orientation exhibited higher buckling strength and lower buckling deformation as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is indicated that using the liner may have some reinforcement effect compared to the pure composite shell. Sumana et al [48] conducted an experimental and numerical comparative study on the buckling of composite cylindrical shells with aluminum liner under external pressure, and found that the cylindrical shells with winding angle of 0 • /90 • have higher buckling strength and lower buckling deformation than those with winding angle of 60 • /30 • , ±45 • and ±55 • . Zuo, Zhang and others [49] carried out a comparative study on steel and steel-composite cylinders under external pressure; three nominally identical steel-composite cylinders and three nominally identical steel ones were tested under uniform external pressure.…”
Section: Elastic Bucklingmentioning
confidence: 99%
“…It is indicated that using the liner may have some reinforcement effect compared to the pure composite shell. Sumana et al [48] conducted an experimental and numerical comparative study on the buckling of composite cylindrical shells with aluminum liner under external pressure, and found that the cylindrical shells with winding angle of 0 • /90 • have higher buckling strength and lower buckling deformation than those with winding angle of 60 • /30 • , ±45 • and ±55 • . Zuo, Zhang and others [49] carried out a comparative study on steel and steel-composite cylinders under external pressure; three nominally identical steel-composite cylinders and three nominally identical steel ones were tested under uniform external pressure.…”
Section: Elastic Bucklingmentioning
confidence: 99%
“…Recently, these forming methods were utilised to form steel-based FMLs, but the latest research papers have been focused mainly on aluminium-based composites. Researchers consider the configuration of the material layers [374][375][376][377] or the process parameter setup [86,[378][379][380][381][382][383][384][385][386] to reduce material defects and go beyond the current forming limits caused mainly by breakage and wrinkling. In order to improve the formability of the layers of FRP, many studies are focused on die forming at elevated temperatures [387][388][389].…”
Section: Die Formingmentioning
confidence: 99%
“…Elements made using this method have superior surface quality and dimensional accuracy. The main obstacle preventing the popularisation of this method is the high cost of the machines and the process, compared with conventional stamping [375]. Fibre orientation has a significant impact on FML performance; Sumana et al [375] produced hydroformed cylindrically shaped FMLs made of 1 mm thick 6061-T6 aluminium alloy and three alternative FRP thicknesses: 1 mm, 2 mm, and 3 mm.…”
Section: Hydroformingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most relevant uncertainties were those related to longitudinal modulus and thickness. Sumana et al [ 6 ] performed finite element instability analysis in composite tubes with a metallic liner (D/t ratios of ca. 40, 26, and 20) and reported up to 9% deviations in relation to experiments.…”
Section: Introductionmentioning
confidence: 99%